2015
DOI: 10.1002/qua.25027
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation and density functional theory insight into the cocrystal explosive of hexaazaisowurtzitane/nitroguanidine

Abstract: Theoretical methods involving molecular dynamics (MD) simulation and density functional theory were performed to investigate the different molecular ratios, mechanical Properties, structure, trigger bond, and intermolecular interaction of hexaazaisowurtzitane (CL-20)/nitroguanidine (NQ) cocrystal explosive. Results of MD simulation show that CL-20 and NQ packed in ratios of 1:1 present the larger binding energy and better mechanical properties than any other molecular ratios, which indicates 1:1 cocrystal can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…Osjetljivost na mehaničke impulse (udar, trenje) je značajno manja u odnosu na osjetljivost CL-20 i približna vrijednostima osjetljivosti za RDX i HMX. Sprovedena je analiza intermolekularnih interakcija koja je uključivala Hiršfeldovu površinsku analizu (Hirshfeld surface analysis), određivanje nekovalentnih regiona i distribuciju elektrostatskog površinskog potencijala [61]. Kokristalna supstanca pod nazivom NEX-1 predstavlja kokristal CL-20/DNMT (1-methyl-3,5-dinitro-1,2,4-triazole) dobijen tehnikom mješanja na bazi rezonantnih akustičnih talasa.…”
Section: Slika 7 Međumolekulske Interakcije Između Susjednih Molekulunclassified
“…Osjetljivost na mehaničke impulse (udar, trenje) je značajno manja u odnosu na osjetljivost CL-20 i približna vrijednostima osjetljivosti za RDX i HMX. Sprovedena je analiza intermolekularnih interakcija koja je uključivala Hiršfeldovu površinsku analizu (Hirshfeld surface analysis), određivanje nekovalentnih regiona i distribuciju elektrostatskog površinskog potencijala [61]. Kokristalna supstanca pod nazivom NEX-1 predstavlja kokristal CL-20/DNMT (1-methyl-3,5-dinitro-1,2,4-triazole) dobijen tehnikom mješanja na bazi rezonantnih akustičnih talasa.…”
Section: Slika 7 Međumolekulske Interakcije Između Susjednih Molekulunclassified
“…In recent years, CL-20-based cocrystals have been researched as a promising strategy to solve the high-sensitivity problem through the method of experiments and simulations. Due to the excellent properties of HMX and its wide application in propellants, , the CL-20/HMX cocrystal has attracted the attention of researchers. Bolton et al reported the cocrystal of CL-20 and HMX, exhibiting a plate habit, and noted that there are CH···O type of hydrogen bonds between CL-20 and HMX molecules .…”
Section: Introductionmentioning
confidence: 99%
“…By now, CL-20 has been found to form cocrystals with a number of other explosives. [11][12][13][14][15][16][17] Although those excellent cocrystals were obtained, the existing preparation methods were still based on a trial-and-error method and cannot realize design or directional preparation of cocrystals completely. It is necessary to understand the competitive relationship between cocrystal and the separate crystals and the formation mechanism of the cocrystal.…”
Section: Introductionmentioning
confidence: 99%